Harnessing oscillatory fluid behaviour to improve debris wash-out in ureteroscopy - Reynolds, Harry C. A.; Turney, Ben W.; Waters, Sarah L.; Moulton, Derek E. (Frontiers in Urology, 2023)
In ureteroscopy, a common method for kidney stone removal, a ureteroscope is inserted into the patient's kidney, through which working tools such as a laser are inserted. During the procedure, the renal space proximal to the scope tip is irrigated with fluid in order to clear stone particles and debris. However, even with continual fluid flow into and out of the kidney, stone dust may become trapped in vortical structures, significantly impairing the operating clinician's field of view. Key to overcoming this challenge is a clear understanding of the flow patterns within an irrigated kidney calyx, and a modelling framework that enables to interrogate how different flow conditions impact on the wash-out time of debris. Previous theoretical studies have uncovered the interplay between fluid structure, in particular the presence of vortical regions, and dust washout, but only in a regime of steady inlet flow conditions. In this paper we model a kidney calyx in an idealised 2D cavity geometry, in which we investigate the presence and potential disturbance of vortical structures due to an oscillatory inlet condition, and the impact on dust washout, modelled as a passive tracer in the flow. By varying the flow amplitude and frequency at the inlet, we uncover a delicate relationship with vortex size and vortex disturbance, and we demonstrate the potential for significant decrease in wash-out time with low-frequency high-amplitude conditions. We then compare this result to the commonly used practice of flushing, a discrete and temporary increase in flow, and we also demonstrate the qualitative robustness of our findings to changes in cavity geometry.